Asking and Answering Questions: Partners, Peer Learning, and Participation - Rivers, John; Smith, Aaron B.; Higgins, Denise; Mills, Ruth; Maier, Alex Gerd; Howitt, Susan Margaret (International Journal for Students as Partners, 2017)
Science is about asking questions but not all science courses provide students with opportunities to practice this essential skill. We give students ownership of the processes of asking and answering questions to help them take greater responsibility for their own learning and to better understand the process of science with its inherent uncertainty. Peer learning activities throughout the course embed multidirectional feedback within and between students and instructors. Students are our partners in the design and evaluation of exam questions and we learn from them as they rise to the challenge of identifying important information and applying it. The lab program is supported by peer assisted learning in which peer mentors partner with instructors to generate activities addressing the use of evidence and experimental design. While not all students engage as partners, those who do value these experiences and demonstrate they can use scientific content creatively and critically.